Effect of conscious abdominal contraction on the activation of periscapular muscles in individuals with subacromial pain syndrome. (April 2021) - de Oliveira Scatolin, Ramon; Hotta, Gisele Harumi; Cools, Ann M.; Custodio, Guilherme Augusto Paiva; de Oliveira, Anamaria Siriani
Abstract: Background: Synergism between shoulder and trunk muscles seems to be effective to increase periscapular muscle activation in asymptomatic subjects. The influence of conscious contraction of the abdominal muscles has not yet been studied in non-athlete subjects with pain. The study aimed to i nvestigate the effect of the instruction for conscious activation of the abdominal muscles on the activity of the scapulothoracic muscles during shoulder exercises in subjects with subacromial pain syndrome. Method: Thirty subjects with unilateral pain (mean age 52 ± 11 years) participated in this study. Three isometric and five dynamic exercises for the scapulothoracic muscles were assessed. The group without instruction just repeated the exercises, while the instruction group was evaluated before and after conscious abdominal training. The linear mixed model analysis was used to compare the muscle activation between groups. Findings: Differences between groups after the conscious abdominal contraction for activation of middle and lower trapezius on the symptomatic side in the "Full can"( p  = 0.03; effect size:0.92 middle trapezius); ( p  = 0.02; effect size:0.96 lower trapezius) and "Knee Push" ( p  = 0.01; effect size:0.75 lower trapezius). For asymptomatic side, the exercises "External Rotation Kneeling" ( p  = 0.04; effect size: 0.81 lower trapezius); ( p  = 0.00; effect size: 2.09 serratus anterior), "Knee Push" ( p  = 0.04; effect size:1.24 serratus anterior) and "Wall Slide" ( p  = 0.01; effect size: 1.03 serratus anterior). Interpretation: Conscious contraction of the abdominal muscle immediately alter the activation of the serratus anterior muscle during closed kinetic chain exercises on the asymptomatic side and increased activation of trapezius on the symptomatic side during shoulder open kinetic chain exercise. Highlights: Additional abdominal contraction increases the activation of the serratus anterior. Additional abdominal contraction increases the activation of the trapezius muscle. Abdominal contraction during "Full Can" exercise influences periescapular activity.